Madura's Cigarette Excise Contribution Amid Illegal Cigarette Pressure - Fatmariyah, Fatimatul; Ahsan, Muhamad; Syarif, Muh; AS, Fathor (MediaTrend, 2024)
The objectives of this study are, 1). Explaining cigarette excise and tariffs, 2). Knowing the number of cigarette companies in Madura, 3). Knowing the circulation of illegal cigarettes in Madura, 4). Knowing the contribution of cigarette excise to the state, 5). Knowing the state losses from illegal cigarettes in Madura. Descriptive qualitative research method. Result 1). Excise tariffs on tobacco products have increased from year to year, 2). The growth of cigarette factories on the island of Madura is very high, 3). The circulation of illegal cigarettes in Madura is very concerning, 4). Madura cigarette excise contribution always exceeds the annual target, and 5). State losses from the circulation of illegal cigarettes in 2021 reached Rp. 3,977,436,785. The limitations of this research are the relatively short research process, the methods used and the limited number of research informants. Future researchers should use other methods with a more significant number of informants. The the oretical implication of this research is that it can add references in the field of excise, and the practical implication is that it can be used as reference material in monitoring the distribution of illegal cigarettes, which is detrimental to the state.